2013
DOI: 10.2109/jcersj2.121.775
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of injectable hydroxyapatite/collagen paste using sodium alginate and influence of additives

Abstract: Preparation of injectable hydroxyapatite/collagen bone-like nanocomposite (HAp/Col) paste utilizing sodium alginate (Na-Alg) and influence of additives on the paste properties were investigated. The HAp/Col at the HAp and collagen mass ratio of 80:20 synthesized by a simultaneous titration method was pelletized to 100212¯m. The HAp/Col powder and that treated with 100 mM CaCl 2 (Ca-HAp/Col) were used as starting powders. A paste was prepared by mixing of the starting powder and Na-Alg solution at one of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition to the results mentioned above, HAp/Col is also expected to be used as a gene transfer bioresorbable substrate based on calcium phosphate-plasmid DNA composite coating method 20,21) and as an injectable material including raw material for rapid prototyping using sodium alginate as lubricant and gelation reagents. 22) Considering its useful properties as a bone substitute, HAp/Col material used for applications discussed in this paper promises far better outcomes for patients than currently used materials.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the results mentioned above, HAp/Col is also expected to be used as a gene transfer bioresorbable substrate based on calcium phosphate-plasmid DNA composite coating method 20,21) and as an injectable material including raw material for rapid prototyping using sodium alginate as lubricant and gelation reagents. 22) Considering its useful properties as a bone substitute, HAp/Col material used for applications discussed in this paper promises far better outcomes for patients than currently used materials.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained HAp/Col was compacted to a disk at 32 mm in diameter and 2 mm in thickness by a uniaxial pressing at 20 MPa for 18 h to squeeze water out of the obtained HAp/Col [17]. The HAp/Col disk was frozen and freeze-dried at −20 • C, crushed by hand, and sorted into 100-212 µm by sieving.…”
Section: Preparation Of Hap/col and Hap/col Powdermentioning
confidence: 99%
“…(1) HAp/Col powders are easily dispersed from the paste mixtures in aqueous solutions, even in highly viscous solutions such as alginate solution [16]. (2) A preliminary anti-washout test for HAp/Col-GTMS pastes prepared with HAp/Col powder, in which collagen molecules were dehydrothermally crosslinked at amino and carboxyl groups, demonstrated rapid decay of the pastes with no retention of any GPTMS gels during the test period.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, HAp/Col is a promising candidate for use as a bioresorbale bone substitute for other materials besides porous materials. We recently reported on HAp/Col pastes using sodium alginate as a hardening agent [16][17][18] and concluded that supplementation of large amounts of calcium salts other than HAp was necessary to obtain sufficient anti-washout properties. Even though the chemicals calcium citrate and calcium carbonate show no harm to tissues, huge amounts of them might decrease and/or inhibit the biological advantages of HAp/Col.…”
Section: Introductionmentioning
confidence: 99%